Determinants of frequency of wine consumption in Croatia - Nenad Vretenar; Jana Katunar; Vinko Zaninović (Ekonomski Vjesnik, 2023)
Purpose: In the last 10 years, wine consumption in Croatia has increased and consumer habits and expectations have changed. Understanding consumer behavior in relation to wine consumption is important for wine-producing countries where wine is an important component of economy. The aim of this study is to identify the factors that influence the frequency of wine consumption in Croatia, where wine production is an important agricultural activity in terms of the number of people employed in the sector and an important factor in the development of tourism. Methodology: Empirical research was conducted by means of a questionnaire filled out by 169 wine consumers who visited a wine fair in the Croatian Adriatic region. Based on the collected data, we developed and estimated a multinomial logit model. Results: The results indicate that wine is consumed more frequently by men, married people, people in long-term relationships, and older people. In addition, people with high levels of education tend to drink wine less frequently. The paper explains the reasons for somewhat puzzling results and suggests future avenues of research. Conclusion: Behavioral differences were confirmed in this study between subsample groups in accordance with four demographic characteristics, i.e., gender, age, marital status, and education criteria. Our analysis showed that males are more likely to consume wine than women, older than younger and less educated than more educated participants. Our results help wine marketers to segment and target wine consumers.